Effect of immobilisation on production of rapamycin by Streptomyces hygroscopicus - Sinha, R.; Srivastava, P. (Cellular and Molecular Biology, 2017)
Numerous antibiotics as secondary metabolites have been isolated from microbes specifically Streptomyces sp. Rapamycin is one of these, which exhibits many roles as immunosuppressant, antifungal antibiotic, anti-tumour etc. Constant thrust has been put by many researchers to improve the production of rapamycin by Streptomyces hygroscopicus. Past research show that whole cell immobilisation is a useful strategy for antibiotic production with economical advantage. This study is another attempt in this direction which involves immobilisation of producer organism on various supports such as polyutherane foam, sintered beads, glass beads and foam peanuts. These support materials have been selected based on their availability and were pre-treated chemically to improve their adsorption capacity. Comparative profiles have been studied to identify the most suited support for the growth of Streptomyces sp. Variation of biomass immobilisation on various support materials with respect to time in batch culture was studied. Cell release study for the carriers was carried out in production medium to evaluate the performance of beads. Also, scanning electron microscopy (SEM) has been employed for visualisation and analysis of immobilised biomass and measurement of pore size. This study aims to determine a suitable support for immobilisation of Streptomyces hygroscopicus which could be used for rapamycin production in batch and continuous mode.